Statistical genetics of infectious diseases - Teo, Yik Ying (Henry Stewart Talks, 2017)
Statistical genetics of infectious diseases, Opportunities & challenges of identifying host genetic factors for infectious diseases, Convergence in evidence between positive selection & host genetic protection to infection, Population genetics of communities facing greater burden of infectious diseases